Fabricating printed circuit boards - Varteresian, Jon. (New York : Newnes, 2002)
Jon Varteresian is owner of JV Enterprises, a company specializing in the design and manufacture of printed circuit boards. He offers numerous tips and techniques from his years of experience that guarantee a smooth and painless PC board design and fabrication process using his step by step approach. Numerous illustrations and photographs demonstrate each step of the process. Topics covered in the book include: safety issues, schematic capture, circuit placement and routing, making printed circuit boards, and plans for projects. An extensive resource list and glossary are also provided. *Gives a complete overview of the printed circuit board design process *Describes how to produce printed circuit boards in small quantities (ideal for prototypes), with an emphasis on safety *Author is owner a company specializing in the design and manufacture of printed circuit boards.
Preface; Overview; Safety; Schematic capture; Circuit board placement and routing; Generating artworks; Developing the resist layer; Etching printed circuit boards; Drilling and shaping; Design; Index.
Includes index.
Keywords: Printed circuits -- Design and construction; Electronic books